Alternative and Authoritative Knowledge: The Role of Certification for Defining Expertise among Doulas. (September 2015) - Henley, Megan M.
Doulas are maternity support workers who provide supportive care to women in childbirth. Doulas do not have medical training, yet they offer an important but underused type of expertise. Certification is not required for work as a doula. This study analyzes the role of certification in legitimating doulas' alternative knowledge about childbirth. Do doulas believe that certification matters for establishing their work as legitimate to mothers and/or to medical clinicians? Certification allows physicians to practice medicine, lawyers to practice law, and teachers to educate students. Why do some doulas get certified by national or international organizations while others do not? To explore these questions, this article uses narrative data from 25 interviews with doulas in the southwestern United States. The majority of these doulas (80 percent) had completed or were in the process of completing their certification. Results indicate that although doulas believe that experience providing support is their primary source of knowledge and defines their expertise among clients, many also argue that certification makes their role legitimate to medical clinicians. Recent changes in health care may give doulas greater access to women most in need of their care, but certification could play a crucial role in gaining this access.